2019
DOI: 10.1007/s13353-019-00521-y
|View full text |Cite
|
Sign up to set email alerts
|

Validation of Diaporthe toxica resistance markers in European Lupinus angustifolius germplasm and identification of novel resistance donors for marker-assisted selection

Abstract: The fungus, Diaporthe toxica, anamorph Phomopsis sp., previously classified as P. leptostromiformis, is a plant endophyte and occasional pathogen, causing Phomopsis stem blight. This disease is damaging not only to lupins but also to the animals grazing on infected plants, due to the toxic secondary metabolites called phomopsins. The aim of this work was to validate markers for resistance to Phomopsis stem blight in narrow-leafed lupins and identify novel germplasm with increased levels of resistance to the di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 48 publications
1
19
0
Order By: Relevance
“…In field conditions, the latent phase lasts until plant maturity [ 20 , 21 , 28 , 29 ]. However, in a greenhouse, with the high humidity favoring fungal development, full disease symptoms are observed on susceptible plants no later than 30 dpi, indicating a considerable reduction of the latent phase [ 30 ]. Termination of the latent phase, which is expected to occur in a greenhouse about 15–20 dpi, would explain this sudden surge in defense response, resulting in the final arrest of the pathogen.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In field conditions, the latent phase lasts until plant maturity [ 20 , 21 , 28 , 29 ]. However, in a greenhouse, with the high humidity favoring fungal development, full disease symptoms are observed on susceptible plants no later than 30 dpi, indicating a considerable reduction of the latent phase [ 30 ]. Termination of the latent phase, which is expected to occur in a greenhouse about 15–20 dpi, would explain this sudden surge in defense response, resulting in the final arrest of the pathogen.…”
Section: Discussionmentioning
confidence: 99%
“…It resulted in the creation of a highly resistant breeding line, 75A:258 [ 23 ]. This genotype was successfully implemented in Australian breeding programs and is still considered as a reference in phytopathological assays because its resistance to D. toxica has never been broken [ 24 , 25 , 26 , 27 , 28 , 29 , 30 ]. It was later revealed that D. toxica resistance in 75A:258 is conferred by a single dominant allele, subsequently named Phr1 [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As seed alkaloid content was reduced by breeding below 0.01% of seed dry weight, a bitter taste, a typical feature of lupins, was fully eliminated from modern cultivars (Kamel et al, 2016). Additionally, the postharvest stubble can be now safety grazed by livestock, because the risk of lupinosis disease was diminished by the introduction of Phomospis stem blight resistance genes (Mulholland et al, 1976;Jago et al, 1982;Cowling et al, 1987;Williamson et al, 1994;Shankar et al, 2002;Ksiażkiewicz et al, 2020). Furthermore, L. angustifolius is currently being promoted in human food markets as a result of its nutritional, metabolomic, and other health benefits (Foyer et al, 2016;Kouris-Blazos and Belski, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Mass sequencing has been exploited in narrow-leafed lupin, to provide several markers linked to anthracnose and Phomopsis stem blight resistance genes. Some of these SNPs were revealed to have a lower recombination rate between the particular trait and marker loci than the previously developed SSR-based markers, and were implemented into breeding practice (Książkiewicz et al 2020 ; Książkiewicz and Yang 2020 ; Yang et al 2015a ; Yang et al 2015b ; Yang et al 2013a ; Yang et al 2013b ; Zhou et al 2018 ). All of these molecular resources have greatly contributed to the improvement of narrow-leafed lupin as a crop.…”
Section: Discussionmentioning
confidence: 99%